Comparative analysis of the influence of biologically active substances on photosynthetic productivity of Sorghum Saccharatum - Gulzhaina, Alpamyssova; Mambetov, Kalmakhan; Dzhakupova, Inkar; Bozhbanov, Alikhan; Dilnoza, Khafizova (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the effects of biologically active substances and varying doses of nitrogen-phosphorus fertilizers on the photosynthetic activity and quality indicators of two sweet sorghum varieties ("Kazakhstanskoye 20" and "Sazhen") and was conducted on heavy loamy sierozems in Southern Kazakhstan’s arid zone. The experimental design included applications of three biostimulants combined with different doses of nitrogen-phosphorus. The complex application of biostimulants and mineral fertilizers significantly enhanced plant development, resulting in increased leaf surface area by 36-76% and photosynthetic potential by 60-112%. The maximum photosynthesis productivity (3.65 g/m²) was achieved when treating seeds with Potassium Humate combined with N₉₀P₉₀ fertilization. Treatment with biostimulants and fertilizers improved the chemical composition and nutritional value of green mass, elevating crude protein content to 12.42% for "Kazakhstanskoe 20" and 12.31% for "Sazhen" varieties. The highest digestible protein content per feed unit (96.5 g and 95.6 g, respectively) was observed with Potassium Humate treatment against the N₉₀P₉₀ background. Strong correlations (r = 0.83-0.98) were established between photosynthetic activity indices and sweet sorghum green mass yield. The combined application of biostimulants, particularly Potassium Humate, with optimal nitrogen-phosphorus fertilization (N₉₀P₉₀) significantly enhances the photosynthetic performance and nutritional quality of sweet sorghum varieties in the arid conditions of Southern Kazakhstan.